Contactless conductivity detector array for capillary electrophoresis. Issue 4 (27th November 2013) - Stojkovic, Marko; Koenka, Israel Joel; Thormann, Wolfgang; Hauser, Peter C.
<x xml:space="preserve">Abstract</x> A CE system featuring an array of 16 contactless conductivity detectors was constructed. The detectors were arranged along 70 cm length of a capillary with 100 cm total length and allow the monitoring of separation processes. As the detectors cannot be accommodated on a conventional commercial instrument, a purpose built set‐up employing a sequential injection manifold had to be employed for automation of the fluid handling. Conductivity measurements can be considered universal for electrophoresis and thus any changes in ionic composition can be monitored. The progress of the separation of Na+ and K+ is demonstrated. The potential of the system to the study of processes in CZE is shown in two examples. The first demonstrates the differences in the developments of peaks originating from a sample plug with a purely aqueous background to that of a plug containing the analyte ions in the buffer. The second example visualizes the opposite migration of cations and anions from a sample plug that had been placed in the middle of the capillary.